PENGARUH NILAI PERUSAHAAN, KINERJA PERUSAHAAN, DAN KESEMPATAN BERTUMBUH TERHADAP RETURN SAHAM PERUSAHAAN KELUARGA DENGAN UKURAN KAP SEBAGAI PEMODERASI - Dea Annisa; Almas Akmarina Nur Alyani (Sekolah Menengah Kejuruan (SMK) Pustek, 2021)
This research was aimed to examine the effect determinant factors of stock return, from the corporate value, corporate performance and growth opportunities. In addition, this research purpose also to find the role of KAP size in moderated relations between the other determinant factors and stock return. This research covers several a family company listed on the Indonesia Stock Exchange (IDX). Role of corporate value proxied by Price Earning Ratio (PER), corporate performance proxied by Return On Asset (ROA), and growth opportunities proxied by Investment Opportunity Set (IOS). KAP size proxied by dummy variabel, score 1 for company that using the big four accountant public and 0 for company that using non the big four accountant public. Stock return proxied by actual return. Variables on this research are be measured by regression analysis and Moderated Regresion Analysis (MRA). Based on the results of the research showed PER, ROA, and IOS had significant effect of the simultaneous on Stock Return. ROA and IOS had significant effect of the parsial on Stock Return. But PER had no significant effect of the parsial on Stock Return. On the results of KAP size able to moderating variable in the relations corporate performance on stock return. But no able to moderating variable in the relations corporate value and growth opportunities on Stock Return